Combined effect of Cinnamomum zeylanicum blume essential oil and nystatin on Candida albicans growth and micromorphology - Castro, Ricardo Dias de; Lima, Edeltrudes de Oliveira; Freires, Irlan de Almeida; Alves, Livia Araújo (Revista de Ciências Médicas e Biológicas, 2013)
Introduction: The combination of a natural product and a synthetic antifungal may lead to a lower dose of each individual agent and consequent reduction of adverse effects and greater pharmacological synergism. Objective: This study investigated the antifungal activity of the essential oil (EO) from Cinnamomum zeylanicum Blume alone and combined with nystatin on Candida albicans growth and micromorphology. Methodology: We determined the Minimum Inhibitory Concentration (MIC), Fractional Inhibitory Concentration Index (FIC) and the effect of the EO alone and combined with nystatin on the growth kinetics and production of virulence-related structures by the yeasts, such as pseudohyphae and chlamydoconidia. Results: When tested alone, the EO from C. zeylanicum and nystatin showed MIC of 312.5 μg/ml and 64 μg/ml, respectively. When combined, MIC values decreased to 39 μg/ml and 32 μg/ml for the EO and nystatin, respectively. The value of the Fractional Concentration Index (FIC) was 0.6024, indicating additivity. It could be observed that at all concentrations the products tested alone and in combination were able to reduce the number of CFU/mL, when compared to the control group (p<0.0001) from 30 min. In addition, both the products alone and combined inhibited production of pseudohyphae and chlamydoconidia compared to the control. Conclusion: The combination between the essential oil from C. zeylanicum and nystatin potentiated the inhibitory effect on C. albicans growth. Furthermore, it reduced the production of pathogenicity-related morphological structures such as pseudohyphae and chlamydoconidia. Key-words: Cinnamomum zeylanicum. Nystatin. Essential Oil. Natural Product. Drug synergism.